2010
DOI: 10.3390/md8040835
|View full text |Cite
|
Sign up to set email alerts
|

Generating a Generation of Proteasome Inhibitors: From Microbial Fermentation to Total Synthesis of Salinosporamide A (Marizomib) and Other Salinosporamides

Abstract: The salinosporamides are potent proteasome inhibitors among which the parent marine-derived natural product salinosporamide A (marizomib; NPI-0052; 1) is currently in clinical trials for the treatment of various cancers. Methods to generate this class of compounds include fermentation and natural products chemistry, precursor-directed biosynthesis, mutasynthesis, semi-synthesis, and total synthesis. The end products range from biochemical tools for probing mechanism of action to clinical trials materials; in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 112 publications
(318 reference statements)
0
36
0
Order By: Relevance
“…42 More importantly, it was identified as a potent 20S proteasome inhibitor and is undergoing clinical trials for the treatment of multiple myeloma. 4,10,48 The proteasome is an ATP-dependent multi-catalytic, multi-subunit protease complex responsible for ubiquitinylation-the process of tagging damaged/unneeded proteins for degradation. 6 Inhibition of the proteasome results in accumulation of intracellular proteins, disrupting cellular homeostasis and ultimately inducing apoptosis.…”
Section: Salinosporamide a And Related Compoundsmentioning
confidence: 99%
“…42 More importantly, it was identified as a potent 20S proteasome inhibitor and is undergoing clinical trials for the treatment of multiple myeloma. 4,10,48 The proteasome is an ATP-dependent multi-catalytic, multi-subunit protease complex responsible for ubiquitinylation-the process of tagging damaged/unneeded proteins for degradation. 6 Inhibition of the proteasome results in accumulation of intracellular proteins, disrupting cellular homeostasis and ultimately inducing apoptosis.…”
Section: Salinosporamide a And Related Compoundsmentioning
confidence: 99%
“…It has been demonstrated that inhibition of the proteasome induces cell death in both normal and neoplastic cells, that cancer cells possess elevated levels of proteasome activity and are more sensitive to proteasome inhibitors than normal cells and, even more, that proteasome inhibition sensitizes neoplastic cells to other proapoptotic stimulus such as chemo o radiation therapy, probably by the NFkappaB pathway. These and other findings provided strong rationale for targeting the proteasome for the treatment of cancer (Voorhees 2006, Potts 2010, Chen 2010b. One of the principal actions of proteasome inhibitors are the regulation of cell cycle control molecules.…”
Section: Proteasome Inhibitors As Anticancer Agentsmentioning
confidence: 99%
“…This process has been named the "ubiquitin-dependent degradation of protein" (Sorokin 2009). Substrates for this non-lysosomal protein degradation pathway include misfolded and defective proteins, as well as others that are selectively polyubiquitin-tagged and targeted for degradation by the ubiquitin-proteasome system (Potts 2010). Proteins differ greatly from each other in lifetime, and the lifetime of protein molecules in an organism depends on their role.…”
Section: The Proteasomementioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the fascinating biological profile and structural complexity has attracted intense interest in the chemical and biological research communities. [91][92][93][94][95][96][97] Our strategy for the synthesis of salinosporamide A (73) relies on racemization-free indium-catalyzed cyclization of chiral amide 84 (Chart 19). We envisaged that the C3 quaternary center could be constructed stereoselectively from cyclized compound 85 by intramolecular delivery of an oxygen atom from the C2 substituent to the exo olefin, and another C4 quaternary center would be created by selective reduction of the ester located in the convex face of the rigid bicyclic structure.…”
Section: Indium-catalyzed Conia-ene Reactions and Total Synthesis Of mentioning
confidence: 99%